2019
DOI: 10.1523/jneurosci.2020-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure Reflects Individual Differences in Music Reward Sensitivity

Abstract: People show considerable variability in the degree of pleasure they experience from music. These individual differences in music reward sensitivity are driven by variability in functional connectivity between the nucleus accumbens (NAcc), a key structure of the reward system, and the right superior temporal gyrus (STG). However, it is unknown whether a neuroanatomical basis exists for this variability. We used diffusion tensor imaging and probabilistic tractography to study the relationship between music rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 67 publications
0
61
3
Order By: Relevance
“…Previous fMRI studies have already shown that these high-order cortical regions involved in auditory cognition and predictive coding show enhanced coupling with reward-related structures, such as the NAcc, while listening to pleasant music (Salimpoor et al, 2013), coinciding with music-induced surprises (Shany et al, 2019). In addition, individual differences in music reward sensitivity are accompanied by similar differences in functional and structural connectivity between the right STG and reward-and emotion-related structures such as the vmPFC, the ventral striatum and the insula (Loui et al, 2017;Martínez-Molina et al, 2019, 2016Sachs et al, 2016). In particular, specific musical anhedonics -individuals who do not derive pleasure from music but show intact music perceptual abilities as well as intact affective reactions to other reward types (Mas-Herrero et al, 2018b, 2014) -showed disrupted auditorystriatal coupling while listening to music.…”
Section: Auditory Cortical Regionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous fMRI studies have already shown that these high-order cortical regions involved in auditory cognition and predictive coding show enhanced coupling with reward-related structures, such as the NAcc, while listening to pleasant music (Salimpoor et al, 2013), coinciding with music-induced surprises (Shany et al, 2019). In addition, individual differences in music reward sensitivity are accompanied by similar differences in functional and structural connectivity between the right STG and reward-and emotion-related structures such as the vmPFC, the ventral striatum and the insula (Loui et al, 2017;Martínez-Molina et al, 2019, 2016Sachs et al, 2016). In particular, specific musical anhedonics -individuals who do not derive pleasure from music but show intact music perceptual abilities as well as intact affective reactions to other reward types (Mas-Herrero et al, 2018b, 2014) -showed disrupted auditorystriatal coupling while listening to music.…”
Section: Auditory Cortical Regionsmentioning
confidence: 96%
“…In particular, specific musical anhedonics -individuals who do not derive pleasure from music but show intact music perceptual abilities as well as intact affective reactions to other reward types (Mas-Herrero et al, 2018b, 2014) -showed disrupted auditorystriatal coupling while listening to music. Conversely, individuals with high sensitivity to music presented the reverse pattern, with greater functional connectivity between auditory cortices and reward centers (Martínez-Molina et al, 2019, 2016. Finally, by combining fMRI with Transcranial Magnetic Stimulation (TMS) over the left dorso-lateral prefrontal cortex, a procedure known to modulate striatal function (Strafella et al, 2001), we have recently provided further evidence in favor of the causal role of auditory-striatal interactions in music-induced pleasure (Mas-Herrero et al, 2018a, Mas-Herrero et al, subm.).…”
Section: Auditory Cortical Regionsmentioning
confidence: 97%
“…A recent group‐level study investigated the connectivity between the STG and NAcc, via the OFC, and how this connectivity varied as a function of individual differences in musical reward . The authors identified a relationship between musical reward, as measured by the BMRQ, and connectivity between the STG and OFC, in a tract that likely passes through the aIns.…”
Section: Experimental Findingsmentioning
confidence: 99%
“…A recent group-level study investigated the connectivity between the STG and NAcc, via the OFC, and how this connectivity varied as a function of individual differences in musical reward. 60 The authors identified a relationship between musical 61 Case Insula/amygdala LH Satoh et al 46 Case Temporoparietal, frontal RH Hirel et al 62 Case Superior temporal gyrus RH Satoh et al 52 Case Putamen RH Belfi et al 50 Group n/a n/a reward, as measured by the BMRQ, and connectivity between the STG and OFC, in a tract that likely passes through the aIns. This relationship was observed only in the right hemisphere-individuals with musical anhedonia showed higher levels of axial diffusivity in this pathway.…”
Section: Neuroimagingmentioning
confidence: 99%
“…These reward-sensitive areas in the dopaminergic network are functionally connected to auditory areas, specifically the superior temporal gyrus, during music listening (Salimpoor et al, 2013;Gold et al, 2019). Hedonic and aesthetic responses to music are related to individual differences in functional connectivity (B. P. Gold et al 2019;Salimpoor et al 2013;Martínez-Molina et al 2019;Sachs et al 2016;King et al 2019) Martinez-Molina et al, 2016 as well as structural connectivity between auditory and reward networks (B. P. Gold et al 2019;Salimpoor et al 2013;Martínez-Molina et al 2019;Sachs et al 2016;King et al 2019), functional connectivity between the nucleus accumbens and the auditory system was found to predict music rewardvalue (Salimpoor et al 2013), while individual differences in white-matter connectivity between superior temporal gyrus, anterior insula, and medial prefrontal cortex were correlated with aesthetic responses to music (Sachs et al 2016).…”
Section: Music Engages Auditory and Reward Systemsmentioning
confidence: 99%